THE DIFFERENT EFFECT OF INSULIN AND GLIBENCLAMIDE ON SKELETAL MUSCLE CELLS - Sri Kentjananingsih, (Matematika dan Sains, 2011)
The propose of research was to being sure in using the suitable medicine for different types of diabetes. This research used randomised control-group pretest-posttest design, almost every-day each of 30 old Norwegian white rats was starved for 2 days and was forced to an exhausted run-walk at least 1.5 hours. It rested 1 hour before it was handled. Results showed that although insulin had its effect only on smashed muscle only on 45 (Hi:H), the effect was seen from 15-45 (Hi:Si). Glibenclamide had its effect faster on smashed muscle (15) rather than on sliced muscle (45) (Hg:H), but the significant difference on both forms muscle had seen on 15 and 30 (Hg:Sg). Both substance effected faster on smashed (from 15-45) (Hig:H), rather than on sliced muscle (only on 45) (Sig:S), but the mixture effect on both forms of muscle had seen from 15-45 (Hig:Sig),. Compared to insulin, their mixture effect showed a significant difference only on sliced muscle 15 (Sig:Si), While the decreasing glucose concentration on sliced and smashed muscle themselves had significant difference from 15-45 (H:S),. Therefore only glibenclamide, works slowly on cell membrane. Both insulin and glibenclaide work inside the cells, but glibenclamide works faster. In their mixture, insulin strengthened the effect of glibenclamide on cell membrane. i:H), the effect was seen from 15-45 (Hi:Si). Glibenclamide had its effect faster on smashed muscle (15) rather than on sliced muscle (45) (Hg:H), but the significant difference on both forms muscle had seen on 15 and 30 (Hg:Sg). Both substance effected faster on smashed (from 15-45) (Hig:H), rather than on sliced muscle (only on 45) (Sig:S), but the mixture effect on both forms of muscle had seen from 15-45 (Hig:Sig),. Compared to insulin, their mixture effect showed a significant difference only on sliced muscle 15 (Sig:Si), While the decreasing glucose concentration on sliced and smashed muscle themselves had significant difference from 15-45 (H:S),. Therefore only glibenclamide, works slowly on cell membrane. Both insulin and glibenclaide work inside the cells, but glibenclamide works faster. In their mixture, insulin strengthened the effect of glibenclamide on cell membrane.